2020
DOI: 10.1186/s12873-020-00335-w
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of tranexamic acid administration in military trauma patients with intracranial hemorrhage: a cohort study

Abstract: Background: Tranexamic acid (TXA) may be a useful adjunct for military patients with severe traumatic brain injury (TBI). These patients are often treated in austere settings without immediate access to neurosurgical intervention. The purpose of this study was to evaluate any association between TXA use and progression of intracranial hemorrhage (ICH), neurologic outcomes, and venous thromboembolism (VTE) in TBI. Methods: This was a retrospective cohort study of military casualties from October 2010 to Decembe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Contrary to other RCTs [39][40][41][42], Chakroun et al demonstrated that TXA increased the incidence of pulmonary embolism in patients with traumatic brain injury [43]. Another retrospective study of 687 wounded soldiers showed that TXA did increase the risk of venous thrombosis [44]. In contrast, a metaanalysis of 30,522 patients in 7 clinical RCTs showed that, despite no statistical difference, the incidence of vascular occlusion in the TXA group was lower than that in the control group [45].…”
Section: Discussionmentioning
confidence: 95%
“…Contrary to other RCTs [39][40][41][42], Chakroun et al demonstrated that TXA increased the incidence of pulmonary embolism in patients with traumatic brain injury [43]. Another retrospective study of 687 wounded soldiers showed that TXA did increase the risk of venous thrombosis [44]. In contrast, a metaanalysis of 30,522 patients in 7 clinical RCTs showed that, despite no statistical difference, the incidence of vascular occlusion in the TXA group was lower than that in the control group [45].…”
Section: Discussionmentioning
confidence: 95%
“…Two RCTs 2,13 were rated as good quality with low risk, whereas there was some concern with 4 RCTs. 3,4,14,15 Nine observational studies 22,23,25,[27][28][29][30]37,40 had a high risk of bias, mainly owing to inadequate handling of confounders, specifically relevant differences in baseline characteristics between intervention and control groups. All results of the meta-analysis are shown in the forest plots in Figure 1, Figure 2, and eFigures 2 to 27 in the Supplement.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Twenty-one studies [2][3][4]13,15,16,[20][21][22][24][25][26]28,[30][31][32][34][35][36][37]39 had reported lower mortality and 9 studies 14,17,19,23,27,29,33,38,40…”
Section: Meta-analysis Of 24-hour Mortality Datamentioning
confidence: 99%
See 1 more Smart Citation
“…77 In the context of military-related TBI with concomitant ICH, TXA has been associated with greater GCS improvement between admission and discharge, although no difference in ICH progression, long-term neurologic outcome, or mortality was observed. 78 However, a meta-analysis examining ICH progression in moderate or severe TBI suggests that TXA may decrease ICH progression in this patient population. [79][80][81] Overall, support for the use of TXA in TBI has continued to increase, highlighting the essential role of the fibrinolytic system in TBI.…”
Section: Tranexamic Acid In Traumatic Brain Injurymentioning
confidence: 99%